Two Neural Circuits to Point Towards Home Position After Passive Body Displacements - Blouin, Jean; Saradjian, Anahid H.; Pialasse, Jean-Philippe; Manson, Gerome A.; Mouchnino, Laurence; Simoneau, Martin (Frontiers in Neural Circuits, 2019)
A challenge in motor control research is to understand the mechanisms underlying the transformation of sensory information into arm motor commands. Here, we investigated these transformation mechanisms for movements whose targets were defined by information issued from body rotations in the dark (i.e., idiothetic information). Immediately after being rotated, participants reproduced the amplitude of their perceived rotation using their arm (Experiment 1). The cortical activation during movement planning was analyzed using electroencephalography and sources analyses. Task-related activities were found in region of interests (ROIs) located in the prefrontal cortex, dorsal premotor cortex, dorsal region of the anterior cingulate cortex and the sensorimotor cortex. Importantly, critical regions for the cognitive encoding of space did not show significant task-related activities. These results suggest that arm movements were planned using a sensorimotor-type of spatial representation. However, when a 8s delay was introduced between body rotation and the arm movement (Experiment 2), we found that areas involved in the cognitive encoding of space (e.g., ventral premotor cortex, rostral anterior cingulate cortex, inferior and superior PPC) showed task-related activities. Overall, our results suggest that the use of a cognitive-type of representation for planning arm movement after body motion is necessary when relevant spatial information must be stored before triggering the movement.